Hábitos del consumo de alcohol en estudiantes de salud de una universidad de la ciudad de Ibarra - Cacuango Cacuango, Anael Vanessa (2024)
In the university environment, alcohol consumption had become a common practice and often considered essential by students. The combination of previous habits, campus freedom, and the availability of alcohol could increase consumption, leading to academic, health, and interpersonal relationship problems. Therefore, it was important to proactively address alcohol consumption in universities. The general objective of the study was to determine the alcohol consumption habits of students of the Higher Technician in Nursing of the Pontifical Catholic University of Ecuador Ibarra in the period from April to August 2024. The study had a quantitative, descriptive, and field approach, with a non-experimental and cross-sectional design. A questionnaire called AUDIT was used to collect and analyze numerical data. The target population was the 284 Health Sciences students of the Higher Technician in Nursing.